The effects of different feeding frequency of Java tilapia, Oreochromis mossambicus, on the production and quality of "Green Water". - Armada, John Francis (UPHSI, 2004)
The study was conducted to determine the effect of different feeding frequency of Oreochromis mossambicus on the production and quality of green water. Green water technology is an innovative technique wherein shrimp are cultured in water collected from a pond where the tilapia and other fishes are grown. This technique is reported to work against luminous bacteria. This study aimed to determine the effect of the different feeding frequency, using commercial feeds, of Oreochromis mossambicus to the production and quality of green water. This study was conducted to determine the mean initial and final biomass, average body weight and survival of sex-reversed tilapia; biological parameters specifically based on phytoplankton density and Chlorella count; Total Vibrio Count as affected by varying feeding frequency; and physico-chemical parameters. The treatments were tested and replicated twice: fed two times, fed four times, and fed six times daily. Statistical tools used include means, ANOVA, and DMRT. Result showed that Treatment 1, twice daily feeding, exhibited a large difference in biological findings: 2.78 x 10^2 cfu/ml, yellow colonies; 7.15 x 10^2 cfu/ml, green colonies; and 3.56 x 10^2 cfu/ml, Total VIbrio Count.